Studying in Times of Crisis : Acculturation and Adaptation of Ukrainian Students at Kraków Higher Education Institutions amidst the COVID-19 Pandemic and Russian Aggression against Ukraine - Klakla, Jan Bazyli, (Educational Research E-Books Online, Collection 2026., 2025)
How do international students cope when crises strike at home and abroad simultaneously? Using vivid firsthand accounts from Ukrainian students studying in Kraków during COVID-19 and Russia's full-scale war on Ukraine, this book investigates the interplay between institutional responses, social support, and individual adaptation strategies. Jan Bazyli Klakla provides fresh qualitative insights into the understudied experiences of student migrants during crisis situations, highlighting practical recommendations for higher education institutions. Essential for scholars, university administrators, and policymakers interested in understanding and supporting international students through challenging times.